Proliferative verrucous leukoplakia: diagnosis, management and current advances - Capella,Diogo Lenzi (2017)
Abstract Introduction: Proliferative verrucous leukoplakia is a multifocal and progressive lesion of the oral mucosa, with unknown etiology, and commonly resistant to all therapy attempts with frequent recurrences. It is characterized by a high rate of oral squamous cell carcinoma and verrucou carcinoma transformations. Objective: To analyze the studies about Proliferative verrucous leukoplakia and develop a concise update. Methods: A Pubmed search identifying studies (laboratory research, case series and reviews of literature) that examined patients with Proliferative verrucous leukoplakia was realized. Results: There are not enough studies about Proliferative verrucous leukoplakia in the literature. The few found studies not present a consensus about its etiology and diagnosis criteria. Although several treatment strategies have been proposed, most of them still show a high recurrence rate. Conclusion: More research about Proliferative verrucous leukoplakia is necessary to understand and treat this disease.